2012
DOI: 10.1016/j.leukres.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential MiRNA expression in childhood acute lymphoblastic leukemia and association with clinical and biological features

Abstract: The present study aimed to analyze the expression profile of the microRNAs previously described as associated with childhood ALL, miR-92a, miR-100, miR-125a-5p, miR-128a, miR-181b, miR-196b and let-7e, and their association with biological/prognostic features in 128 consecutive samples of childhood acute lymphoblastic leukemia (ALL) by quantitative real-time PCR. A significant association was observed between higher expression levels of miR-196b and T-ALL, miR-100 and patients with low white blood cell count a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 48 publications
8
85
3
2
Order By: Relevance
“…mir-125a-5p is downregulated in many cancers (de Oliveira et al ., 2012; Sand et al ., 2012), which strongly suggests that mir-125a-5p functions as a suppressor of proliferation and migration in cancer cells. In noncancer cells, mir-125a-5p mediates lipid uptake, decreases the secretion of inflammatory cytokines (IL-2, IL-6 and TNF-α) and the expression of oxysterol binding protein-like-9 (ORP9) in human monocytic cells (Chen et al ., 2009), and suppresses ET-1 expression in human umbilical vascular endothelial cells (HUVECs) (Li et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…mir-125a-5p is downregulated in many cancers (de Oliveira et al ., 2012; Sand et al ., 2012), which strongly suggests that mir-125a-5p functions as a suppressor of proliferation and migration in cancer cells. In noncancer cells, mir-125a-5p mediates lipid uptake, decreases the secretion of inflammatory cytokines (IL-2, IL-6 and TNF-α) and the expression of oxysterol binding protein-like-9 (ORP9) in human monocytic cells (Chen et al ., 2009), and suppresses ET-1 expression in human umbilical vascular endothelial cells (HUVECs) (Li et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in miRNA expression patterns and their respective targets have been documented in various tumors [12] including different types of leukemias such as chronic lymphocytic leukemia [13], acute myeloid leukemia [14] and ALL [15], thus suggesting a possible correlation between miRNA expression status and the development of hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The association between the lower expression of miR-128 and steroid resistance was not evaluated in the present study. In these and other previous studies, miR-128 expression did not correlate with other biological and clinical features (28,31). The role of miR-128 insufficiency in the pathogenesis and response to treatment in patients with IKZF1-deletion ALL should be additionally examined with large-scale pediatric patients with ALL.…”
Section: Discussionmentioning
confidence: 54%
“…In a comparison between normal controls and patients with AML, an increased expression of miR-128 in patients with ALL has been suggested (26). Altered miR-128 expression may discriminate ALL from adult myeloid leukemia and normal bone marrow samples (27)(28)(29)(30). Notably, Mi et al (27) revealed that the differential expression of miR-128 in acute leukemia is not a consequence of an altered genomic DNA copy number, and suggested that this miRNA is also under other types of DNA epigenetic regulation.…”
Section: Discussionmentioning
confidence: 99%